Interaction of a hydrophobic-functionalized PAMAM dendrimer with bovine serum albumin thermodynamic and structural changes - Zhang, Hong-Mei (Langmuir : the ACS journal of surfaces and colloids, 2014)
The interaction between a hydrophobic-functionalized PAMAM dendrimer (PAMAM-NH2-C12, 25%, G4) and bovine serum albumin (BSA) has been investigated by circular dichroism (CD), UV-vis, and fluorescence spectroscopic methods and molecular modeling. The analysis of the effects of dendrimer complexation on the stability and conformation of BSA indicated that the binding process of the hydrophobic-functionalized dendrimer with BSA induced the relatively large changes in secondary structure of protein. Thermal denaturation of BSA, when carried out in the presence of dendrimer, also indicated that this hydrophobic-functionalized dendrimer acted as a structure destabilizer for BSA. The hydrophobic, electrostatic, and hydrogen bonding forces played important roles in the complex formation. The putative binding site of PAMAM-NH2-C12 (25%) dendrimer on BSA was near to domain I and domain II. The effect of hydrophobic modification on the stability and structure of BSA would find useful information on the cytotoxicity of PAMAM dendrimer